가스 파이프라인용 30인치 볼 밸브의 누설량 평가 - 김철규(Chul Kyu Kim); 이상문(Sang Moon Lee); 장춘만(Choon Man Jang) (한국수소 및 신에너지학회 논문집, 2016)
The purpose of this study is to evaluate the gas leakage for a 30-inch ball valve. The ball valve was designed and manufactured for a natural gas transportation through a long-distance pipeline mainly installed in the permafrost region. The gas leakage assessment is based on the pressure testing criteria of international standards. Pressure conditions of the gas leakage test was employed 70 bar, 100 bar, and 110 bar. The amount of the gas leakage at each pressure condition was small and had a value under the pressure testing criteria, ISO 5208. Gas leakage with respect to the test pressure was predicted by the polynomial curve fitting using the experimental results. It is found that the gas leakage rate according to the pressure is proportion to a second order curve.